2021
DOI: 10.1111/anec.12824
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic markers of increased risk of sudden cardiac death in patients with COVID‐19 pneumonia

Abstract: Background: LittleisknownabouttheroleofECGmarkersofincreasedriskofsud-dencardiacdeathduringtheacuteperiodofcoronavirusdisease2019(COVID-19) pneumonia. Objectives: ToevaluateECGmarkersofsuddencardiacdeathonadmission,includingtheindexofcardiacelectrophysiologicalbalance(iCEB)(QTc/QRS)andtransmuraldispersionofrepolarization(TDR)(Tfrompeaktoend(Tp-e)intervalandTp-e/ QTc),inpatientswithCOVID-19pneumonia. Patients and methods: This cross-sectional study included 63 patients with newly diagnosedCOVID-19pneumoniawhopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Previous studies reported that prolonged QT is associated with ventricular arrhythmias and cardiovascular mortality [ 19 ]. It was also reported that QRS time and QT/QTc are increased in COVID-19 patients [ [20] , [21] , [22] ]. In the present study, we found that QT/QTc and QRS time increased significantly in the patient group compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that prolonged QT is associated with ventricular arrhythmias and cardiovascular mortality [ 19 ]. It was also reported that QRS time and QT/QTc are increased in COVID-19 patients [ [20] , [21] , [22] ]. In the present study, we found that QT/QTc and QRS time increased significantly in the patient group compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID‐19), the illness caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), mainly affects the respiratory system and shows wide range of clinical presentations varying from asymptomatic/mild symptoms to severe viral pneumonia with respiratory failure, systemic inflammatory syndrome, and death (Gorbalenya et al, 2020 ; Wang et al, 2020 ; Zhou et al, 2020 ). Although the respiratory tract is the primary target for SARS‐CoV‐2 virus, cardiovascular involvement has been documented in acute phase of the disease in different studies (Alareedh et al, 2020 ; Madjid et al, 2020 ). In recovered patients, palpitations and dyspnea on exertion may prolong and adversely affect health even after full recovery from COVID‐19.…”
Section: Introductionmentioning
confidence: 99%
“…We have read with great interest the article “Electrocardiographic markers of increased risk of sudden cardiac death in patients with COVID‐19 pneumonia” by Alareedh et al, ( 2021 ).…”
mentioning
confidence: 99%